Qailulah dalam Perspektif Hadis: Analisis Tematik dan Relevansinya terhadap Pencegahan Burnout Akademik Mahasiswa di Era Digital - Lasmiati Radiah; Ahmad Rayhan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines the concept of qailulah from a hadith perspective and its relevance to preventing academic burnout in students in the digital era. This study falls within the field of Hadith Studies with an interdisciplinary approach that connects hadith teachings with mental health issues in higher education. This study aims to analyze hadiths about qailulah thematically and examine their relevance in addressing academic burnout due to the high demands of study and the use of digital technology. The study used a qualitative approach with library research methods. Data were obtained from hadiths about qailulah in various hadith books and scientific literature on student mental health. The analysis was conducted using the thematic hadith method to gain a comprehensive understanding. The results show that qailulah is not only a form of worship but also functions as an energy management strategy and maintains a balance of activities, thus potentially helping reduce the risk of academic burnout in students in the digital era.